The Opposition of East and West in the Long Day Wanes Novel by Anthony Burgess - Zinnatullina, Zulfiya; Khabibullina, Liliya; Popp, Ivan (Journal of History Culture and Art Research, 2017)
This year the literary public celebrates 100th anniversary of Anthony Burgess’ birth (1917-1993). The trilogy The Long Day Wanes is among early works of the author, but also the author considers perspective of the East and the West relationship here. In the article we consider the main lines of the characters representing the mother country and colony, also we designate evolution of heroes in the trilogy and we draw a conclusion on as far as the writer departs from the traditional ways the East-common English literature depicting in the first half of the 20th century. It is possible to allocate two tendencies of the East assessment in the trilogy: image of Asians as slowwitted and silly and, on the contrary, strange, difficult representatives of an exotic mentality. There is no uniformity in the image of colonialists. Some Europeans and British feel "at home", being in East space, like culture and mentality of the East, and some represent type of the colonialist treating everything as an object to study. The special attention is deserved by any representatives of "false" identity having lost themselves in someone else’s system of values.